A Novel Chemoattractant Lectin, Karatoxin, From the Dorsal Spines of the Small Scorpionfish Hypodytes rubripinnis - Mitsuko Shinohara; Kuniko Nagasaka; Hideyuki Nakagawa; Kozue Edo; Hitomi Sakai; Koji Kato; Futoshi Iwaki; Kiyoshi Ohura; Haruhiko Sakuraba (Elsevier, 2010)
A chemoattractant lectin from the dorsal spines of the redfin velvetfish, Hypodytes rubripinnis, was isolated using a combination of affinity chromatography techniques. The glycoprotein, with a molecular mass of 110 kDa, is named Karatoxin. Karatoxin caused agglutination of rabbit erythrocytes. This agglutination was effectively inhibited by d-mannose. In addition, Karatoxin exhibited not only mitogenic activity in the presence of murine splenocytes, but also chemotactic activity in the presence of guinea-pig neutrophils and macrophages. Thus, Karatoxin appears to be a novel chemoattractant lectin. These results suggest that the redfin velvetfish Hypodytes rubripinnis may be a novel source of biologically active substances. Keywords:: chemoattractant lectin, Karatoxin, Hypodytes rubrinnis